Pengembangan Website Ramah Disabilitas Sebagai Media Aktualisasi Diri Penerima Manfaat di Panti Pelayanan Sosial "Pendowo" Kabupaten Kudus - Muhammad Sholikhan; Nur Fajrie; Imaniar Purbasari (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Disability groups often face social stigmatization and obstacles in achieving self-actualization. Limited support and accessibility to knowledge, facilities and policies that support individual needs is a major problem. The state has a responsibility to respect the rights of disabled groups, including humane treatment, equal fulfillment of life, and survival. Improving the quality of services for disability beneficiaries is key through social innovation and rehabilitation. The role of government institutions is to improve skills for independence. Communication and education of service programs are important, and several programs have helped beneficiaries self-actualize. In the context of the "Pendowo" Social Services Home for Disabilities in Kudus Regency, there are barriers to access to information and communication with the community. Therefore, creating a website using the WordPress CMS with a responsive template has succeeded in overcoming this problem. This website facilitates registration of potential beneficiaries, provides information resources, and allows interaction via web service technology. This creates a dual benefit by increasing convenience and accessibility for all parties involved.